Confrontation, cooptation and collaboration: the response and reaction of the Labour Party of South Africa to Government Policy, 1965-1984 - Du Pré, Roy Howard (Rhodes University, Faculty of Humanities, Department of History, 1995)
The Labour Party was a prominent political party amongst coloured people for more than twenty-five years. Formed in 1965 to contest elections for the Coloured Persons' Representative Council (CRC), the Labour Party at the outset adopted an anti-apartheid, anti-separate representation and anti-eRe stance. During the first five years of its existence, the party tried to muster coloured support for its policies. Its promise to cripple the CRC by refusing to occupy seats in the council became the rallying call. The Labour Party won a majority of the elected seats in the first CRC election in 1969 but the government nominated progovernment candidates to all the nominated seats, depriving the Labour Party of an overall majority. Thwarted in their bid to "wreck" the CRC, Labour Party members instead took their seats in the council, vowing to destroy it from within. For the next five years the Labour Party pursued a policy of "confrontation. " By using a "boycott" strategy, it not only hamstrung the effective working of the CRC but thwarted the government in other areas of its "coloured" policy. In the 1975 election the Labour Party won an outright victory, giving it the power to cripple the CRC. However, it did not seize this opportunity. Its decision to "govern" in the CRC constituted a decisive step in the change from confrontation to cooptation. The Labour Party's continued support of the CRC drew widespread criticism from supporters and opponents alike. Its leaders tried to hold together a disaffected party and eventually agreed to the dissolution of the CRC in 1980 in an effort to paper over the cracks in party unity, and to forestall growing coloured opposition to the CRC at the next election. In 1983, the Labour Party displayed a decisive shift in its anti-separate representation stance by lending support to the tricameral system. By doing so, it laid itself open to the same charge of collaboration it had levelled at the other CRC parties. This thesis will examine the history of the Labour Party from its formation in 1965 as an anti-government party, to one of cooperation with its erstwhile opponent by 1984.
Keywords: South African Labour Party; Colored people (South Africa) -- Politics and government; South Africa -- Politics and government -- 1948-1994